Impact of Applying a Skin Compression With the Ultrasound Probe on Carotid Artery Strain Elastography. (14th May 2021) - Chayer, Boris; Roy Cardinal, Marie‐Hélène; Biron, Vicky; Cloutier, Noémie; Petit, Clara; Dubord, Samuel; Allard, Louise; Cloutier, Guy
Abstract : Objective: To study the impact of varying the external compression exerted by the ultrasound probe when performing a carotid strain elastography exam. Methods: Nine healthy volunteers (mean age 43 years ±13 years; 6 men) underwent a vascular ultrasound elastography exam using a custom made sound feedback handle embedding the probe, and allowing the sonographer to adjust the applied compression. A clinical standard practice (SP) force was first recorded, and then predetermined compression (PDC) forces were applied, ranging from 0 to 5 N for the left common carotid artery (CCA) or 2–12 N for the left internal carotid artery (ICA). Six carotid elastography features, namely maximum and cumulated axial strains, maximum and cumulated shear strains, cumulated axial translation, and cumulated lateral translation were assessed with noninvasive vascular elastography (NIVE) on near and far walls of carotids. The carotid intima media thickness (IMT) and diameter were also measured. Results: All elastography features on the near wall of both CCA and ICA decreased statistically significantly as the PDC force increased; this association was also observed for half of the features on the far wall. Three NIVE features at the lowest PDC force (out of 72 that were tested) were statistically significantly different than values at the SP force. Overall, NIVE showed some variance to probe compression with linear regression slopes revealing changes of 10.1%–45.6% in magnitude over the whole compression range on both walls. The maximum IMT for the ICA near wall, and carotid lumen diameters of both CCA and ICA were statistically significantly associated with PDC forces; these features underwent a decrease of 10.2%, 36.2%, and 17.6%, respectively, over the whole range of PDC force increase. Other IMT measurements were not statistically significantly associated with applied PDC forces. Conclusion: These results suggest the need of technical guidelines for carotid strain elastography. Using the lowest probe compression while allowing a good B‐mode image quality is recommended to improve the robustness of NIVE measurements.